Clinical trait-specific genetic analysis in Behçet's disease identifies novel loci associated with ocular and neurological involvement - ALİBAZ ÖNER, FATMA (My University, 2023)
Behçet’s disease is a complex inflammatory vasculitis with a broad spectrum of clinical manifestations. The purpose of this study was to investigate the genetics underlying specific clinical features of Behçet’s disease in a group of patients with > 20 years of follow up. A total of 436 patients with Behçet’s disease from Turkey were studied. Genotyping was performed using the Infinium ImmunoArray-24 BeadChip. After imputation and quality control measures, logistic regressions adjusting for sex and the first five principal components were performed for each clinical trait using a case-case genetic analysis approach. A weighted genetic risk score was calculated for each clinical feature. Genetic association analyses of previously identified susceptibility loci in Behçet’s disease revealed a genetic association between ocular lesions and HLA-B/MICA (rs116799036: OR=1.85, 95% CI=1.35-2.52, p-value=1.1x10-4 ). The genetic risk score was significantly higher in Behçet’s disease patients with ocular lesions compared with those without ocular involvement, and is explained by the genetic variation in the HLA region. New genetic loci predisposing to specific clinical features in Behçet’s disease were suggested when genome-wide variants were evaluated. The most significant associations were observed in ocular involvement with SLCO4A (rs6062789: OR=0.41 (95% CI=0.30-0.58), p-value=1.92x10-7 ), and neurological involvement with DDX60L (rs62334264: OR= 4.12 (95% CI 2.34 to 7.24), p-value = 8.85x10-7 ). Our results emphasize the role of genetic factors in predisposing to specific clinical manifestations in Behçet’s disease, and might shed additional light into disease heterogeneity, pathogenesis, and variability of Behçet’s disease presentation across populations.
Keywords: Behçet’s disease; clinical manifestations; genetics; HLA; ocular lesions